The female poisoner’s fate: accounting for lenient outcomes in New South Wales, Australia, 1855-1955 - Strange, Carolyn (Crime, histoire & sociétés, 2023)
Most scholarly histories of the female poisoner use high-profile cases to explore the cultural, social, political and legal construction and repercussions of women’s poisoning crimes. Yet, the study of notorious poisoners has obscured how most women tried for poisoning were treated by the courts. By deploying a longitudinal analysis of women prosecuted for murder or attempted murder by poisoning, this article challenges the feminist historiographical and criminological consensus that women poisoners are invariably demonised by the press and subjected to harsh penalties by the courts. It examines the former penal colony of New South Wales, Australia, from the mid-1800s to the mid-1950s, over which time 47 women were prosecuted and just one was executed. Through four case studies, it illustrates the prosecution outcomes that befell most women tried for poisoning. This lenience cannot be attributed solely to the race, ethnicity, class, and sexual respectability of women on trial for poisoning. Analysing the female poisoner’s fate must also take into consideration victim-offender relationships, the purported motives of accused women, the nature of specific poisons, the statutory framing of poisoning, and the shifting context of penal politics.